Motivasi Belajar yang Rendah pada Anak Keluarga Broken Home - Pungki Ariska, Sekar (Green Publisher Indonesia, 2024)
This study was conducted with the aim of determining the causes of low learning motivation in children from broken homes. This study uses a qualitative research type with a case study method. This study was located in Cicau Village, Central Cikarang. The Selection of subjects used 3 informants, namely SD as an older sister, MD as a younger brother, and R as SD and MD is mother, data collection using interview and observation techniques with the result of the study, subjects SD and MD have low motivation due to parental factors who do not give enough attention to children and always fight in front of SD and MD. Research in Cicau Village, Central Cikarang shows that children from broken home families tend to receive less attention and encouragement in education, which has an impact on low motivation to learn, decreased achievement, and indifference to learning.